GOVERNANCE ISSUES IN MANAGING ZAKAT FUNDS: THE EXPERIENCE OF SELECTED ZAKAT MANAGEMENT INSTITUTIONS IN MALAYSIA - Mohamad, Shamsher; Muhamad Sori, Zulkarnain (I-iECONS e-proceedings, 2023)
Technically, zakat means a fixed proportion of wealth collected from the rich individuals to help the poor and in need so that the recipients purify their hearts from the feelings of envy, jealousy and anger towards the rich. It is the third pillar of Islam that address the economic inequality gap in a Muslim society, and its importance is indicated by the fact that it is not only mentioned at least 58 times in the Quran, but the potential recipients of zakat are clearly identified. The main responsibility of managing the collection and distribution of Zakat funds is on the state governments that have set up designated zakat institutions to perform this important religious responsibility. To ensure that the zakat institutions dispense their responsibilities in the best way possible without fear or favour to assist the poor and the underprivileged, there is a need for a proper zakat management system with good governance practices that properly incorporates the attributes of transparency, accountability, efficiency and fairness. A well-managed zakat institution with proper governance will not only instil public confidence and trust in these institutions but serve the objectives of zakat as ordained by Allah in the Quran. This paper deliberates on the issues of governance in the collection and distribution of Zakat Funds at selected Zakat institutions in Malaysia. It highlights some important governance issues that need immediate attention for Zakat institutions to dispense their responsibilities in a more transparent and efficient manner. The current mode of administration of zakat funds has significantly contributed to these issues. Some solutions are suggested to address the highlighted issues in view of improving the transparency and efficiency in administrating zakat funds at these official zakat centers.